Strigolactones are common regulators in induction of stomatal closure in planta. (4th March 2018) - Zhang, Yonghong; Lv, Shuo; Wang, Guodong
ABSTRACT: Strigolactones (SLs) have been implicated in many plant biological processes, including growth and development and the acclimation to environmental stress. We recently reported that SLs intrinsically acted as prominent regulators in induction of stomatal closure. Here we present evidence that the effect of SLs on stotamal closure is not limited to Arabidopsis, and thus SLs could serve as common regulators in the modulation of stomatal apertures of various plant species. Nevertheless, TIS108, a SL-biosynthetic inhibitor, exerted no effect on stomatal apertures. In addition, the SL receptor mutant atd14-5, similar to SL-deficient and more axillary growth 2 ( max2 ) mutants, exhibited hypersensitivity to drought stress. Altogether, these results reinforce the role of SLs as common regulators in stress resilience.